Do Green Finance and Green Innovation Enhance Sustainable Investment Decisions? Identifying The Pivotal Role of Artificial Intelligence - Maya Novitasari; Syaiful Bahri; Dwi Sulistiani; Yona Octiani Lestari; Moawiah Alghizzawi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
This quantitative study aims to empirically examine the effects of green finance and green innovation on sustainable investment decisions, as well as the role of artificial intelligence in moderating these relationships. The population consisted of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Purposive sampling was employed to select 427 companies for observation. Data were analysed using CEM panel data regression. The results reveal that both green finance and green innovation positively affect sustainable investment decisions, and artificial intelligence can moderate these impacts. The study findings offer valuable insights for companies operating in Indonesia’s non-cyclical consumer sector. Green innovation can be applied as a green finance policy to improve sustainable investment decisions. Furthermore, artificial intelligence can be used to strengthen the influence of green finance on sustainable investment decisions. This study, therefore, supports the triple bottom line and the Sustainable Development Goals, encouraging companies in Indonesia not only to focus on profits but also to increase their environmental awareness.